Starting a business 101 : from creating a business plan and sticking to a budget to marketing and making a profit, your essential primer to starting a business - Cagan, Michele (Adams Media, 2023)
This indispensable guide for those looking to start their own business provides all the essential information for overcoming any obstacle thrown in their way during the process.